Sacred Spaces, Shared Souls: Interfaith Harmony at Taman Kemaliq Lingsar, Lombok, Indonesia - Sumertha, I Wayan; Busro, Busro; Wibisono, M. Yusuf (Jurnal Ilmiah Peuradeun, 2025)
This study examined the phenomenon of socio-religious interaction between the Hindu and Islamic communities of Wetu Telu in Taman Kemaliq Pura Lingsar, Lombok. Using a qualitative approach, this study aimed to understand how Taman Kemaliq becomes an acculturation space that facilitates and reflects interfaith harmony. The research uncovered shared histories and religious practices that affirmed communal identity and religious tolerance through in-depth interviews, participatory observations, and document analysis. The results showed that Taman Kemaliq is a place for religious rituals and a symbol of harmony and collective identity. Simultaneous religious practices, such as rarak kembang waru ceremonies for Muslims and odalan ceremonies for Hindus, provide a platform for both communities to express their own beliefs and traditions while strengthening social relations between communities. This research found that Taman Kemaliq was a sacred place that united differences through ritual practices and strengthened tolerance and harmonious interaction between religious communities in daily life. The study offered new perspectives on religious and cultural practices as tools of inclusive social development and their potential to inspire interfaith harmony. These findings are important for anthropological, theological, and cultural studies, and they show that Taman Kemaliq can be a real example of multicultural societies managing diversity and creating harmony.